COMPARATIVE ANALYSIS AND NUTIRITIONAL COMPOSITION OF MULBERRY FRUIT MORUS ALBA PLUS SEABUCKTHORN (HIPPOPHAE) AND THEfR PRODUCTS - Alizai, Mohammad Nisar; Rehman, Shamsur; Shah, Wazir Hussain (Biological Sciences - PJSIR, 2003)
The!huts of mulbe produced III Northern Pakis1a11,,ere subiected 10 hol air dehydration 10 preserve without losing its narural flavour and nutrienls. The dehydrated mulbeny powder "hieh 1s called mulberry bevcrngc base (MOB) yielded eood frmt tast\ drink when mixed with sui1able amount of waler.Shcll:lile assessment was also conducted. The fresh fruil ;xtraet and th dehydrated mulbe·beverage base (MJ38) ,,ere analysed for juice,pulp, MBB, moisture, acidity as cilrie acid, 101al soluble solids. sugar.;, ascorbic acid and ash minerals like calcium. potassium, phosphorous, sodium and iron in fresh fruit extract was also dctcrmmcd. Muibe pulp "as mixed w11h seabucl..thorn pulp prior to dehydra1ion Dehy drated product \\BS found bcner in 1aste.colour and lla,our.